2011
DOI: 10.1086/656575
|View full text |Cite
|
Sign up to set email alerts
|

Ovulation, Female Competition, and Product Choice: Hormonal Influences on Consumer Behavior

Abstract: Recent research shows that women experience nonconscious shifts across different phases of the monthly ovulatory cycle. For example, women at peak fertility (near ovulation) are attracted to different kinds of men and show increased desire to attend social gatherings. Building on the evolutionary logic behind such effects, we examined how, why, and when hormonal fluctuations associated with ovulation influenced women's product choices. In three experiments, we show that at peak fertility women nonconsciously c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
171
4
6

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 259 publications
(194 citation statements)
references
References 63 publications
(66 reference statements)
13
171
4
6
Order By: Relevance
“…These results support previous speculation that testosterone plays a key role in regulating women's intrasexual competitiveness (Cobey et al, 2013), but calls into question the suggested role of estradiol in women's relationship jealousy (Cobey et al, 2011;Geary et al, 2001). While previous research on changes in women's intrasexual competitiveness has highlighted links with estimated fertility (Durante et al, 2008(Durante et al, , 2011Fisher, 2004;Haselton et al, 2007;Lucas & Koff, 2013;Vukovic et al, 2009), our study is the first to demonstrate correlated changes in intrasexual competitiveness and natural variation in women's testosterone levels.…”
Section: Hahn 15supporting
confidence: 87%
See 2 more Smart Citations
“…These results support previous speculation that testosterone plays a key role in regulating women's intrasexual competitiveness (Cobey et al, 2013), but calls into question the suggested role of estradiol in women's relationship jealousy (Cobey et al, 2011;Geary et al, 2001). While previous research on changes in women's intrasexual competitiveness has highlighted links with estimated fertility (Durante et al, 2008(Durante et al, , 2011Fisher, 2004;Haselton et al, 2007;Lucas & Koff, 2013;Vukovic et al, 2009), our study is the first to demonstrate correlated changes in intrasexual competitiveness and natural variation in women's testosterone levels.…”
Section: Hahn 15supporting
confidence: 87%
“…Similarly, premenopausal women are more likely to derogate other women's attractiveness than are postmenopausal women (Vukovic et al, 2009). Increases in intrasexual competitiveness around ovulation, such as those described above, are suggested to occur because successful competition for mating opportunities with high-quality mates is more likely to translate into fitness benefits at this time (Durante et al, 2008(Durante et al, , 2011Fisher, 2004;Haselton et al, 2007;Lucas & Koff, 2013;Vukovic et al, 2009). …”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…They spend moue time in looking fou cosmetics, fashion, ounamental stuff like jeweluy, and at least spend moue money in such activities. The authous of this wouk conclude that these behavious aue houmonally influenced and expuess female competition fou mating pautneus (Duuante & Guiskevicius, 2016;Duuante et al, 2010).…”
Section: Women Advertising During Different Cycle Phasesmentioning
confidence: 76%
“…During the late follicular period, women experience a peak in estrogen followed by a rise in progesterone; which is associated with a marked increase in sexual interest during this phase (Durante, Griskevicius, Hill, Perilloux, & Li, 2011). However, this research is inconsistent.…”
Section: The Role Of Waist-to-hip Ratio and Menstrual Cycle Phasementioning
confidence: 99%